Medidas processuais de contenção da alta litigiosidade - Felix, André Salgado (2022)
It is no secret that we have the largest litigation in the world, the current scenario of repetitive litigation calls for urgent solutions. We have transformed the Judiciary into an industry, with annual expenditures exceeding R$100 billion and 77 million2 active court lawsuits. Access to the Judiciary does not represent the fast resolution of conflicts of those who most need the State intervention. The studies presented here seek solutions, within the civil procedural system, that reduce the high rate of judicialization without hampering the citizen's access to justice, guaranteed by the Constitution and fundamental in the a Democratic State. We will mention (i) justice free of charges and “Juizados Especiais”; (ii) alternative conflict solutions; and the main one, (iii) the Repetitive Demand Resolution Incident (IRDR), inserted in the repetitive question judgment microsystem. This dissertation aims to analyze the effects of the these procedural instruments, in the current litigation society, focusing on the perspective of the new system of precedents and its prestige to the principles of legal certainty, isonomy and reasonable duration of the process